Establishment and Evaluation of a Novel Method Based on Loop-Mediated Isothermal Amplification for the Rapid Diagnosis of Thalassemia Genes - Wang W; Lin M; Li H; Huang J; Chen J; Fang X; Huang D; Xi X; Zhao Q; Song F; Huang S; Zhong T (Dove Medical Press, 2020)
Wei-hua Wang,1,* Min Lin,2,* Hai-liang Li,3 Jun-yun Huang,1 Jiang-tao Chen,4,5 Xian-song Fang,6 Dong-mei Huang,1 Xu-xiang Xi,1 Qing-fei Zhao,1 Fang-li Song,7 Shao Huang,7 Tian-yu Zhong1 1Department of Laboratory Medicine, First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi Province, People’s Republic of China; 2School of Food Engineering and Biotechnology, Hanshan Normal University, Chaozhou, Guangdong Province, People’s Republic of China; 3Department of Hematology, First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi Province, People’s Republic of China; 4The Chinese Medical Aid Team to the Republic of Equatorial Guinea, Guangzhou, Guangdong Province, People’s Republic of China; 5Department of Medical Laboratory, Huizhou Central Hospital, Huizhou, Guangdong Province, People’s Republic of China; 6Department of Blood Transfusion, First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi Province, People’s Republic of China; 7Jiangxi Shiningmed Medical Technology Ltd, Ganzhou, Jiangxi Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shao HuangJiangxi Shiningmed Medical Technology Ltd, Ganzhou, Jiangxi Province, People’s Republic of ChinaTel +86-18602004914Email huangshao@shiningmed.comTian-yu ZhongDepartment of Laboratory Medicine, First Affiliated Hospital of Gannan Medical University, Ganzhou 341000, Jiangxi, People’s Republic of ChinaTel +86-797-8680632Email zhongtianyu@126.comPurpose: Currently, thalassemia is commonly detected using gap-polymerase chain reaction (PCR) and deoxyribonucleic acid (DNA) reverse dot blot, which have high requirements of space, instruments, and personnel. Therefore, it is necessary to develop a new method for thalassemia detection with high sensitivity, low cost, and simple and fast operation. In this study, we aimed to design and evaluate a new method for detecting three α-thalassemia genes including –Southeast Asian (SEA), -α 3.7, and -α 4.2 and five β-thalassemia genes including 654M, 41/42M, − 28M, 17M, and  27/28M based on loop-mediated isothermal amplification (LAMP).Methods: Primer sequences were designed using Primer Explorer V4 software. Blood samples (5 mL) were collected from all participants in EDTA. DNA was extracted using Chelex 100 and was subjected to LAMP. LAMP products were detected by fluorescence development in ultraviolet light.Results: We found that LAMP assays for positive samples of thalassemia reached a plateau before 60 minutes, whereas the negative control samples entered the plateau after 70 minutes or showed no amplification. The concentration range of positive reactions was between 20– 60 pg/μL and 20– 60 ng/μL. Additionally, there were no cross-reactivities among 8 thalassemia subtypes. For clinical samples, the positive sample tube showed strong green fluorescence, whereas the negative tube showed light green fluorescence. According to these results, the LAMP method has high sensitivity for detecting thalassemia (252/254). However, 43 false-positive results were obtained in the LAMP test. The LAMP assay was also of low cost and with simple and fast operation.Conclusion: The novel LAMP assay can be completed within 60 min using a heating block or a water bath, and the result can be read visually based on color change to detect thalassemia. The LAMP assay fulfills the requirements of field application and resource-limited areas, especially those with primary hospitals and rural areas.Keywords: loop-mediated isothermal amplification, diagnosis, thalassemia genes, fast, low cost